(untitled) (Journal of Engineering, 2023)
One-third of the total waste generated in the world is construction and demolition waste. Reducing the life cycle of building materials includes increasing their recycling and reuse by using recycled aggregates. By preventing, the need to open new aggregate quarries and reducing the amount of construction waste dumped into landfills, the use of recycled concrete aggregate in drum compacted concrete protects the environment. Four samples of PRCC were prepared for testing (compressive strength, tensile strength, flexural strength, density, water absorption, porosity) as the reference mix and (10, 15, and 20%) of fine recycled concrete aggregate as a partial replacement for fine natural aggregate by volume. The mix is designed according to (ACI 327-15) with the specified cylinder compressive strength (28 MPa). The results showed a decrease in mechanical properties with an increase in partial replacement compared to the reference mixture and an increase in water absorption and porosity at 28 days. This is because old cement mortar on the surfaces of fine recycled concrete aggregates leads to higher porosity and water absorption than fine natural aggregates. At 90 days, results improved slightly. This is due to the non-aqueous cement in the recycled fine concrete aggregate.